Index based assessment of coastal vulnerability along the West Coast of Peninsular Malaysia: evidence of climate change and anthropogenic impacts - Ganugapenta, Sreenivasulu; Ariffin, Effi Helmy; Li, Wenjian; Zainuddin, Siti Nur Hanani; Jefri Din, Mohammad Ikhmal Siddiq; Menhat, Masha Nur Salsabiela; Mohd Zaki, Nurwani; Mokhtar, Mardiha; Razali, Muhammad Rizal; Abdul Maulud, Khairul Nizam; Miskon, Mohd Fuad (Elsevier Ltd., 2026)
Coastal areas are increasingly threatened by the combined effects of climate change and human activities. This study investigates coastal vulnerability along the West Coast of Peninsular Malaysia (WCPM) by applying a comprehensive Coastal Vulnerability Index (CVI) that integrates multiple physical and socio-economic variables. A total of fourteen parameters were assessed, including nine physical parameters such as bathymetry, shoreline change, sea level rise, geomorphology, and mangrove cover, along with five socio-economic parameters such as infrastructure, population density, and land use. Principal Component Analysis and hierarchical cluster analysis were applied to identify the most influential factors and reveal spatial patterns of vulnerability. The results showed that districts in the northern region exhibit very high vulnerability due to the combination of sensitive environmental features and intense human pressures, particularly rapid infrastructure development. In contrast, southern districts tend to have lower vulnerability, supported by natural buffers and relatively less disturbance. A two-way hierarchical heatmap provided insights into regional groupings and co-occurring vulnerability drivers. The resulting risk map serves as a practical decision-making tool to support adaptive coastal planning. It can help stakeholders and policymakers prioritize areas for intervention, implement zoning regulations and adopt nature-based solutions to enhance resilience against future coastal hazards.